2023
DOI: 10.5582/bst.2023.01133
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the female genital tract and gut microbiome on reproductive dysfunction

Wenli Cao,
Xiayan Fu,
Jing Zhou
et al.

Abstract: Microorganisms are ubiquitous in the human body; they are present in various areas including the gut, mouth, skin, respiratory tract, and reproductive tract. The interaction between the microbiome and reproductive health has become an increasingly compelling area of study. Disruption of the female genital tract microbiome can significantly impact the metabolism of amino acids, carbohydrates, and lipids, increasing susceptibility to reproductive tract diseases such as vaginitis, chronic endometritis, endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Some scholars have found that the proportion of Escherichia/Shigella and the number of Streptococcus in intestinal growth, whereas the number of Akkermansia and Ruminococcaceae decreases in patients with Polycystic ovary syndrome ( Liu et al, 2022 ). An increase in the number of Escherichia coli and Shigella in the gut microbiome of patients with stage IIIIV endometriosis was found ( Ata et al, 2019 ; Cao et al, 2024 ). Escherichia coli can also cause chronic endometritis ( Cao et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some scholars have found that the proportion of Escherichia/Shigella and the number of Streptococcus in intestinal growth, whereas the number of Akkermansia and Ruminococcaceae decreases in patients with Polycystic ovary syndrome ( Liu et al, 2022 ). An increase in the number of Escherichia coli and Shigella in the gut microbiome of patients with stage IIIIV endometriosis was found ( Ata et al, 2019 ; Cao et al, 2024 ). Escherichia coli can also cause chronic endometritis ( Cao et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of Escherichia coli and Shigella in the gut microbiome of patients with stage IIIIV endometriosis was found ( Ata et al, 2019 ; Cao et al, 2024 ). Escherichia coli can also cause chronic endometritis ( Cao et al, 2024 ). To our knowledge, this is the first time Escherichia/Shigella has been found to negatively affect menstruation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations